2022
DOI: 10.1111/nph.18460
|View full text |Cite
|
Sign up to set email alerts
|

SnRK1A‐mediated phosphorylation of a cytosolic ATPase positively regulates rice innate immunity and is inhibited by Ustilaginoidea virens effector SCRE1

Abstract: Rice false smut caused by Ustilaginoidea virens is becoming one of the most recalcitrant rice diseases worldwide. However, the molecular mechanisms underlying rice immunity against U. virens remain unknown.Using genetic, biochemical and disease resistance assays, we demonstrated that the xb24 knockout lines generated in non-Xa21 rice background exhibit an enhanced susceptibility to the fungal pathogens U. virens and Magnaporthe oryzae. Consistently, flg22-and chitininduced oxidative burst and expression of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…As a Ser/Thr protein kinase, SnRK1 mainly functions by phosphorylating serine and threonine residues of substrate proteins. [ 46 , 47 , 48 ] To explore whether TaSnRK1α−1A could phosphorylate TaPAP6L‐2B, we transfected proteins of tobacco leaf cells with 35S::GFP‐TaSnRK1α‐His and 35S::GFP‐TaPAP6L‐Flag. Immunoprecipitation with anti‐Flag antibody, and detection by immunoblots with Pan anti‐phosphorylation and anti‐Flag antibody showed that the addition of TaSnRK1α−1A significantly improved the phosphorylation level of TaPAP6L‐2B ( Figure 4 A ), suggesting that TaPAP6L‐2B was an endogenous substrate of TaSnRK1α−1A.…”
Section: Resultsmentioning
confidence: 99%
“…As a Ser/Thr protein kinase, SnRK1 mainly functions by phosphorylating serine and threonine residues of substrate proteins. [ 46 , 47 , 48 ] To explore whether TaSnRK1α−1A could phosphorylate TaPAP6L‐2B, we transfected proteins of tobacco leaf cells with 35S::GFP‐TaSnRK1α‐His and 35S::GFP‐TaPAP6L‐Flag. Immunoprecipitation with anti‐Flag antibody, and detection by immunoblots with Pan anti‐phosphorylation and anti‐Flag antibody showed that the addition of TaSnRK1α−1A significantly improved the phosphorylation level of TaPAP6L‐2B ( Figure 4 A ), suggesting that TaPAP6L‐2B was an endogenous substrate of TaSnRK1α−1A.…”
Section: Resultsmentioning
confidence: 99%
“…Another model is the immune response mediated by the SnRK1A-XB24 phosphorylation cascade signalling pathway ( Figure 2 b). Yang et al [ 57 ] found that SnRK1A, a conserved energy-regulating protein in eukaryotes, interacts with XB24 and phosphorylates its Thr83 amino acid to improve its ATPase activity and regulate the immune signalling pathway of rice. During the early stage of infection, SCRE1 specifically interacts with XB24 in rice, blocking the binding of XB24 to ATP and inhibiting its hydrolysis of ATP.…”
Section: Genetic Mechanism Of the Immune Response To Rfsmentioning
confidence: 99%
“…Rice false smut caused by Ustilaginoidea virens has emerged as one of the most important rice diseases and poses a significant economic impact on rice commercial production worldwide (Brooks et al., 2010 ; Fan et al., 2016 ; Tanaka et al., 2008 ). Ustilaginoidea virens infects and colonizes rice florets with hyphae, which are eventually transformed into false smut balls covered with powdery chlamydospores (Fan et al., 2020 ; Sun et al., 2020 ; Yang, Zhang, Wang, et al., 2022 ; Zheng et al., 2022 ). False smut balls contain a large amount of mycotoxins that not only deteriorate grain quality but also threaten the health of both animals and people (Fu et al., 2018 ; Guo et al., 2012 ; Zhang et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%